Waste Management of COVID-19 Personal Protective Equipment in Indonesia and the Potential for Globally Oriented Development - Mikha Meilinda Christina; Twin Yoshua Raharjo Destyanto; Lenny Halim (Fakultas Teknik, 2023)
The use of Personal Protective Equipment (PPE) can protect against exposure to the COVID-19 virus, but on the other hand it causes an increase in the generation of plastic waste. The amount of COVID-19 PPE waste is estimated at 1.6 million tons per day with masks or face shields worth 3.4 billion per day. The urgency of handling PPE waste is not only due to the volume of waste, but also the nature of the virus that survives on solid surfaces. This publication aims to provide a systematic review of PPE waste management in Indonesia, both from health facilities and households. Good practices from abroad are explored to see the potential for developing PPE waste management in Indonesia. The search results provide 38 articles, namely 21 national articles and 17 international articles. PPE waste management in Indonesia and abroad in general is separation, disinfection, collection/temporary storage, transportation, and final disposal (incineration/sterilization/landfill). 3R practice improvement (reuse, reduce, recycle) can create sustainable PPE waste management, for example, the use of environmentally friendly materials, reuse PPE after sterilization to increase lifetime or conversion of PPE waste into raw materials.